(untitled) (Research, Society and Development, 2024)
Introduction: The article contextualizes what Oppositional Defiant Disorder (ODD) is and analyzes the most recent studies on non-pharmacological treatment options for ODD. The work also considers the possible genetic and physiological factors involved in the pathophysiology of ODD. It highlights the importance of early diagnosis and adherence to Cognitive Behavioral Therapy (CBT) and its different forms of presentation. Aim: The main objective was to explore safe and effective therapeutic approaches for treatment with children that are individualized and tailored to the needs that each child demands. Methodology: The study was conducted through qualitative research of literature reviews in databases such as Scielo, Pubmed, Medline, and Google Scholar, as well as in child psychiatry books. Results: The present article highlights that CBT, combined with parental support and educational interventions, effectively reduces ODD symptoms and improves the behavior and quality of life of children affected by the disorder. Conclusion: It is concluded that these findings reinforce the importance of considering therapeutic approaches adapted to the specific needs of each child with ODD, seeking to maximize therapeutic outcomes and improve long-term quality of life.